Assessing Quality of Life, Menopausal Symptoms, and Coping Strategies among Menopausal Women: A Cross-Sectional Study in Cumilla, Bangladesh - Mili, Jasrin Akter; Munny, Mashuma; Rahman, Dilara; Mazumder, Nazma; Nasreen, SK Zinnat Ara (Central Medical College Journal, 2024)
Background: Menopause is a natural biological transition that can significantly impact a woman's quality of life due to associated physiological, psychological, and social changes. In Bangladesh, there is a lack of awareness and understanding about menopause and its health implications. This study aimed to assess the health-related quality of life, prevalence of menopausal symptoms, coping mechanisms, and associated socio-demographic factors among menopausal women in the South Sadar region of Cumilla, Bangladesh. Methods: This cross-sectional, quantitative study was conducted at the Central Medical College & Hospital in Cumilla from October 2023 to March 2024. The sample included 400 women aged 40-59 years who had experienced natural menopause at least one year prior. Data was collected through face-to-face interviews using a structured questionnaire, the Menopausal Rating Scale (MRS) for assessing quality of life and symptom severity, and a coping mechanisms checklist. Descriptive statistics, chi-square, and Fisher's exact tests were used for data analysis. Results: This community-based study included 400 postmenopausal women aged between 40-59 years (mean 53.51 ± 3.43 years). The prevalence of menopausal symptoms based on the Menopausal Rating Scale (MRS) was high, with 75.5% experiencing somatic symptoms, 69.8% psychological symptoms, and 49.3% urogenital symptoms. The most common symptoms were joint/muscular discomfort (60.3%), anxiety (50.8%), and bladder problems (35.3%). The mean total MRS score of 9.5 ± 5.3 indicated a moderate-to-severe symptom burden. A staggering 70.25% of women had poor quality of life related to menopausal symptoms. Factors significantly associated with poor quality of life included rural residence (p=0.014), lower education (p<0.001), being a housewife or laborer (p=0.003), divorced/separated/widowed status (p=0.031), marriage before age 20 (p=0.009), lack of physical activity (p=0.018), and presence of chronic health problems (p=0.021). Commonly adopted coping strategies were dietary modifications (11.25%), physical activity (10%), yoga/meditation (6.25%), and Ayurvedic/herbal remedies (5%). However, 32.5% did not use any specific coping mechanism. The findings highlight the high burden of menopausal symptoms, suboptimal quality of life, and the influence of socioeconomic disadvantages on menopausal health in this population. Conclusion: The findings provide insights into the prevalence of menopausal symptoms, coping strategies, and the impact on health-related quality of life among postmenopausal women in South Sadar, Cumilla. Central Medical College Journal Vol 8 No 1 January 2024 Page: 23-34